Amplification of drawdown and runup over Hawaii's insular shelves by tsunami N-waves from mega Aleutian earthquakes. (April 2018) - Bai, Yefei; Yamazaki, Yoshiki; Cheung, Kwok Fai
Highlights: A mega Aleutian earthquake generates a dispersive leading tsunami wave followed by a prominent trough. The tsunami trough shows little attenuation across the ocean due to absence of side lobes and dispersive properties. Upswing of the impulsive drawdown generated by the trough over Hawaii's insular shelves produces unprecedented runup. Abstract: The latest tsunami evacuation maps of Hawaii include an extreme scenario triggered by an Mw 9.3 Aleutian earthquake with large near-trench rupture. The tectonic plate motion produces concentrated seafloor uplift toward the deepest part of the trench generating a tsunami with strong non-hydrostatic characters. A parametric study shows the skewed seafloor uplift produces a dispersive leading crest followed by a prominent trough in the form of an N -wave. The trough maintains its depth across the ocean in the absence of side lobes and dispersion. Shifting of the uplift toward the trench tends to deepen the trough, but has diminishing effects on the wave crest away from the source. While the attenuated leading crest produces relatively moderate runup on north-facing shores of the Hawaiian Islands, with matching of the N -wave and shelf resonance periods, the trough produces an impulsive drawdown followed by an energetic upswing with unprecedented runup for a far-field tsunami. A set of control computations without dispersion reaffirms that a non-hydrostatic model is essential to account for these complex wave processes from the source to the shore. This case study highlights the unique tsunami hazards posed by the Aleutians to Hawaii and the role of wave troughs in delineating the impacts for hazard assessment and engineering design.